Nonsynostotic Cranial Deformity: A Six-Month Matched-Pair Photogrammetric Comparison of Treated and Untreated Infants. (November 2014) - Wilbrand, J.F.; Hagemes, F.; Wilbrand, M.; Kühnemann, J.; Dey, F.; Streckbein, P.; Howaldt, H.P.
Objective: To photogrammetrically objectify changes in nonsynostotic craniofacial deformity in orthotically treated versus untreated infants. Design: A statistical retrospective pairwise comparison of two respective three-dimensional (3D) photo scans of 80 children performed in a 6-month time lag. Patients: Two comparable samples of children (40 treated, 40 untreated) with nonsynostotic cranial deformity. Interventions: Respective 3D photo scans were matched using Cranioform Analytics 4.0 software. Main Outcome Measures: Median change of 30° Cranial Vault Asymmetry Index (CVAI), modified CVAI (CVAImod ), Cranial Index (CI), and posterior symmetry ratio (PSR). Results: We found an improvement in Δ30° CVAI by 3.3% (treated) and by 1.31% (untreated), respectively. CVAImod improved by 3.46% in the treated group and by 1.55% in the untreated group. CI improved by 4.41% in the treated group and by 3.68% in the untreated group, and PSR improved by 0.71 in the treated group and 0.49 in the untreated group. Although improvement of cranial asymmetry was higher in those children treated with an individual molding orthosis, we could not document a statistically significant difference between the two groups. Conclusions: Helmet therapy may be less appropriate for the correction of brachycephaly than for cranial asymmetry. Nonsynostotic cranial deformity shows some spontaneous correction. Photogrammetry presents an accurate method to objectify craniofacial changes in early infancy.